L’arakanisation d’Arakan : les racines d’un nouvel exode ? - Maxime Boutry (L'Espace Politique)
The conflict opposing Buddhist and Muslim populations in Rakhine State (Arakan) since June 2012 is different from the previous ones for its national knock-on effects and a generalization of the confrontations to the Muslim populations of Myanmar. Nonetheless, political analyses omit to take into account the ethnic complexity and the fluidity of identities characterizing Arakan populations: they cannot be summarized to the sole Arakanese and Rohingya like they cannot be classified simply between Buddhists and Muslims. This article tries to explain this long-standing complexity that allowed interethnic exchanges despites splitting imaginaries and the effects of essentialist discourses linked to the conflict on the relationship between these populations and the Rakhine territory. The current identities’ idealization process tending to deprive any other population than Arakanese Buddhists from legitimacy on the Rakhine territory will be determining in shaping the constantly increasing Rohingya emigration.